2017
DOI: 10.1159/000467896
|View full text |Cite
|
Sign up to set email alerts
|

MiR-142-3p Overexpression Increases Chemo-Sensitivity of NSCLC by Inhibiting HMGB1-Mediated Autophagy

Abstract: Background: Non-small-cell lung cancer (NSCLC) is a deadly cancer with high mortality rate. Drug resistance represents a main obstacle in NSCLC treatment. High mobility group box-1 (HMGB1) protein promotes drug resistance in NSCLC cells by activating protective autophagy. Methods: In the current study, we investigated the regulatory role of microRNA-142-3p (miR-142-3p) in HMGB1-mediated autophagy of NSCLC cells and its impact on drug resistance of NSCLC in vitro and in vivo. HMGB1 was identified as a putative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
51
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(54 citation statements)
references
References 43 publications
3
51
0
Order By: Relevance
“…A number of studies have demonstrated that the PI3K/AKT/mTOR signaling pathway is excessively activated in tumors, induces tumorigenesis and promotes tumor progression [29, 30]. Under physiological conditions, PI3K/AKT signaling pathway is one of the important signal transduction pathways and plays a key role in inhibiting apoptosis and promoting proliferation by affecting the activation state of various downstream effector molecules [31].…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies have demonstrated that the PI3K/AKT/mTOR signaling pathway is excessively activated in tumors, induces tumorigenesis and promotes tumor progression [29, 30]. Under physiological conditions, PI3K/AKT signaling pathway is one of the important signal transduction pathways and plays a key role in inhibiting apoptosis and promoting proliferation by affecting the activation state of various downstream effector molecules [31].…”
Section: Discussionmentioning
confidence: 99%
“…Most recent, miR-142-3p has been reported to be associated with several types of cancer. MiR-142-3p was significantly upregulated in renal cell carcinoma and miR-142-3p inhibitor could significantly suppressed cell migration and proliferation, and promoted cell apoptosis in 786-O and ACHN cells [30]; miR-142-3p was down-regulated in both cancer cell lines and cancer specimens and miR-142-3p overexpression suppressed proliferation by leading cell cycle arrest in G2/M [31]; miR-142-3p was downregulated in hepatocellular carcinoma (HCC) tissues and the overexpression of miR-142-3p inhibited aerobic glycolysis and thus proliferation of HCC cells by targeting lactate dehydrogenase A (LDHA) [32]; miR-142-3p was significantly lower in ovarian cancer tissues and cell lines and Ectopic expression of miR-142-3p significantly inhibited the proliferation of ovarian cancer cells by targeting sirtuin 1 (SIRT1) and increased the sensitivity of SKOV3/DDP cells to cisplatin [33]; miR-142-3p was markedly downregulated in gastric cancer tissues and could inhibit the proliferation, invasion and migration of gastric cancer cells [34]; miR-142-3p inhibited proliferation and invasion in HeLa and SiHa cells by targeting frizzled 7 receptor [FZD7] [35]; miR-142-3p miR-142-3p downregulated MGMT expression and also sensitizedGlioblastoma multiforme [GBM] cells to alkylating drugs [36]; miR-142-3p overexpression increased PI3K, Akt, and mTOR phosphorylation by targeting High mobility group box-1 [HMGB1] in NSCLS cells [37]. According to CRC, three studies have suggested that miR-142-3p is involved in CRC development.…”
Section: Discussionmentioning
confidence: 99%
“…The regulatory role of miR-142-3p has been reported in several types of cancer. For example, miR-142-3p overexpression increases the chemosensitivity of non-small cell lung cancer (NSCLC) by inhibiting high-mobility group box 1-mediated autophagy Chen et al [14]. In addition, it can modulate osteosarcoma progression by interacting with metastasisassociated lung adenocarcinoma transcript-1 Liu et al [15].…”
Section: Introductionmentioning
confidence: 99%